Integrated charge sensitive amplifier «Tetrod-JFET» and its application for research of diamond charged-particles detectors - Afanaciev, Konstantin G.; Batouritski, Mikhail A.; Emeliantchik, Igor F.; Litomin, Alexander V.; Solin, Alexander V. (Journal of the Belarusian State University. Physics, 2018)
Integrated charge sensitive amplifier «Tetrod-JFET», which was developed by «National Center for Particle and High Energy Physics», BSU and produced by JSC «Integral» within the framework of collaboration in the Large Hadron Collider program, is described. Research of diamond charged-particles detectors is presented. Effective charge collection distance, the main parameter determining the quality of diamond detector, is measured. The procedure includes measurements of the charge created by a minimum ionization particle and its conversion to the charge collection distance using the known number of electron-hole pairs generated by the minimum ionization particle per unit length of the diamond transversing.